2020
DOI: 10.12669/pjms.36.3.1820
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between the mineral drinking water composition and the relevance of dentine in health – A pilot study

Abstract: Objective: This study estimated the concentration of Ca, Mg and F in drinking water from five counties in Transylvania, Romania and correlated these with mineral values found in the dentine of permanent carious teeth. The role of these minerals on the re-mineralization of teeth is broadly analyzed. Methods: The study consists of two parts: the first part is a pilot study aimed at determining the concentration of Ca, Mg and F in the dentine of permanent carious teeth of 75 male adults with residence in fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…There is a relationship between fluoride from water and dentin. [ 22 ] Fluoride ions are antimicrobial, so they can reduce the number of bacteria that cause dental caries and gingivitis. [ 23 ] The results of the research show that the causes of gingivitis in peatlands are the presence of calculus on the necks of the teeth, a lack of fluoride in saliva, and the viscosity of saliva, which causes dirt on the necks of the teeth to stick and cause irritation to the gingiva.…”
Section: Discussionmentioning
confidence: 99%
“…There is a relationship between fluoride from water and dentin. [ 22 ] Fluoride ions are antimicrobial, so they can reduce the number of bacteria that cause dental caries and gingivitis. [ 23 ] The results of the research show that the causes of gingivitis in peatlands are the presence of calculus on the necks of the teeth, a lack of fluoride in saliva, and the viscosity of saliva, which causes dirt on the necks of the teeth to stick and cause irritation to the gingiva.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, low mineral content in drinking water, such as calcium and magnesium, has been found to have various adverse health impacts. Associated health risks include an increased risk of cardiovascular disease [18][19][20][21][22][23], caries [24,25], osteoporosis [26,27] and potentially various cancers [28][29][30][31][32][33]. This could be relevant in the Gaza Strip because of the high consumption of desalinated water [4].…”
Section: Potential Health Risks Associated With Drinking Water Qualit...mentioning
confidence: 99%
“…The effects of drinking RO water on dental health are a subject of interest, particularly in relation to calcium (Ca), magnesium (Mg), and fluoride (F) concentrations. Drinking water with appropriate levels of Ca, Mg, and F creates an environment conducive to remineralization in oral tissues, promoting dental health [ 10 ]. A study conducted by Razvan et al [ 10 ] suggests that drinking water with Ca and Mg levels below recommended standards may not adequately support tooth remineralization.…”
Section: Reviewmentioning
confidence: 99%
“…Drinking water with appropriate levels of Ca, Mg, and F creates an environment conducive to remineralization in oral tissues, promoting dental health [ 10 ]. A study conducted by Razvan et al [ 10 ] suggests that drinking water with Ca and Mg levels below recommended standards may not adequately support tooth remineralization. Furthermore, studies have indicated that the presence of calcium in drinking water can decrease the development of dental caries, as measured by the decayed, missing, and filled tooth surfaces (DMF-S).…”
Section: Reviewmentioning
confidence: 99%